2005
DOI: 10.1016/j.nuclphysa.2005.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Strangeness in neutron stars

Abstract: We discuss the role of strangeness on the internal constitution and structural properties of neutron stars. In particular, we report on recent calculations of hyperon star properties derived from microscopic equations of state for hyperonic matter. Next, we discuss the possibility of having a strange quark matter core in a neutron star, or the possible existence of strange quark matter stars, the so-called strange stars.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On top of that, if the electron (e − ) chemical potential grows with increase of the baryon density in the neutron star, the Σ − hyperon may be formed through the weak interaction, n + e − → Σ − + ν. Furthermore, it is suggested that the Σ − may appear at a lower density earlier than the Λ in spite of the fact that the Σ − is more massive than the Λ [2]. It is also suggested that the Ξ − hyperon may appear at a relatively low density depending on the strength of Ξ − attraction in the interior of the neutron star [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, if the electron (e − ) chemical potential grows with increase of the baryon density in the neutron star, the Σ − hyperon may be formed through the weak interaction, n + e − → Σ − + ν. Furthermore, it is suggested that the Σ − may appear at a lower density earlier than the Λ in spite of the fact that the Σ − is more massive than the Λ [2]. It is also suggested that the Ξ − hyperon may appear at a relatively low density depending on the strength of Ξ − attraction in the interior of the neutron star [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Many scenarios for the GRB have been proposed: the "collapsar", or "hypernova" model linking the GRB with ultra-bright type Ibc supernovae (hypernovae) and the subsequent black hole formation 1 [4]; neutron star mergers [5], or accretion of matter onto a black hole; strange star collisions [6]; the model [7] assuming a large surface magnetic field up to 10 16 G of a millisecond pulsar produced in the collapse of a ∼ 10 9 G white dwarf, with a powerful pulsar wind, as the source of the GRB; the model [8] suggesting a ee + plasma wind between heated neutron stars in close binary systems as consequence of the ν ν annihilation; the model [10] of a steadily accreting ∼ 10 6 G white dwarf collapse to a millisecond pulsar with a ∼ 10 17 G interior toroidal field, causing the GRB; an (isotropic) first order phase transition [11] of a pure hadronic compact star to a strange star (see also [12]); asymmetric core combustion [13] in neutron stars due to the influence of the magnetic field generating an acceleration of the flame in the polar direction, etc.…”
Section: Introductionmentioning
confidence: 99%